Turismo y desarrollo de zonas marginales, caso de estudio; muelle recreativo de Playa Grande del cantón Quevedo, año 2013-2014 - Franco Morán, Indary Roberta (2015)
The thesis aims to study, analyze and understand the situation on tourism and development of the marginal zone, case study; Playa Grande recreational pier Quevedo Canton sector. Currently there are potential opportunities and benefits that tourism can offer; and therefore the socio-economic and cultural improvement of its people. At the conclusion of this thesis, to convert the aforementioned tourist potential and is a practical contribution as a source of income. To investigate what is the importance, characteristics and perspectives presents sustainable and viable today. The hypothesis is aimed to publicize the municipal authorities and citizens of Playa Grande sector and instead work with and offer ideas to improve the service offered on the welfare of the entire population Quevedeña and therefore the development and growth of the Tourists in the city. The research contains 8 chapters; Chapter I: the contextual framework of research that supports description of the problems exposed. The general and specific objectives arise; and it is justified by the great importance of the tourism project as it allows appreciate the interest in the study area. Chapter II: presenting theories of some authors, besides the legal framework. Chapter III: general description of the materials and methods is made; the research design and sample surveys the silver in this study. Chapter IV: The results and discussion are presented and the SWOT matrix was applied to determine the real situation. Chapter V: the proposal as an alternative solution, Tourism Development Plan is included to improve the provision of services on dock Recreativo de Playa Grande. Chapter VI: The conclusions and recommendations were recorded related to evidence the research study and fulfillment of the objectives. Chapter VII: the source with the APA and lincografia, Chapter VIII develops contains the annexes of the investigation.